Movement order and saccade direction affect a common measure of eye-hand coordination in bimanual reaching - Mooshagian, Eric (American Physiological Society, 2014)
Studies of visually guided unimanual reaching have established that a saccade usually precedes each reach and that the reaction times (RTs) for the saccade and reach are highly correlated. The correlation of eye and hand RT is commonly taken as a measure of eye-hand coordination and is thought to assist visuospatial guidance of the hand. We asked what happens during a bimanual reach task. As with a unimanual reach, a saccade was executed first. Although latencies were fastest on unimanual trials, eye and hand RT correlation was identical whether just one or both hands reached to a single target. The average correlation was significantly reduced, however, when each hand reached simultaneously to a different target. We considered three factors that might explain the drop. We found that correlation strength depended on which hand reached first and on which hand reached to the same target as the saccade. Surprisingly, these two factors were largely independent, and the identity of the hand, left or right, had little effect. Eye-hand correlation was similar to that seen with unimanual reaching only when the hand that moved to the same target as the saccade was also the first hand to move. Thus both timing as well as spatial pattern are important in determining eye-hand coordination.